2022
DOI: 10.3389/fphar.2022.903259
|View full text |Cite
|
Sign up to set email alerts
|

Allicin in Digestive System Cancer: From Biological Effects to Clinical Treatment

Abstract: Allicin is the main active ingredient in freshly-crushed garlic and some other allium plants, and its anticancer effect on cancers of digestive system has been confirmed in many studies. The aim of this review is to summarize epidemiological studies and in vitro and in vivo investigations on the anticancer effects of allicin and its secondary metabolites, as well as their biological functions. In epidemiological studies of esophageal cancer, liver cancer, pancreatic cancer, and biliary tract cancer, the antica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 199 publications
1
21
0
Order By: Relevance
“…Treatment with the extracts or compounds derived from Allium has been the subject of numerous studies and trials to establish a link with a reduced risk of cancer. In this sense, our findings are in concordance with other assays previously published [ 39 , 40 , 41 ]. In fact, several in vitro and in vivo studies have shown the potential antiproliferative activity of the extracts or compounds derived from Allium in the same cell lines we have tested.…”
Section: Discussionsupporting
confidence: 94%
“…Treatment with the extracts or compounds derived from Allium has been the subject of numerous studies and trials to establish a link with a reduced risk of cancer. In this sense, our findings are in concordance with other assays previously published [ 39 , 40 , 41 ]. In fact, several in vitro and in vivo studies have shown the potential antiproliferative activity of the extracts or compounds derived from Allium in the same cell lines we have tested.…”
Section: Discussionsupporting
confidence: 94%
“…As one of the most widely grown ingredients in the world, allicin has good bioavailability and bioequivalence (Lawson and Hunsaker, 2018), which makes it easy for people to obtain allicin compared with other probiotics with strict requirements. In fact, allicin is widely used in the clinic for cancer, cardiovascular disease, cold, hypertension, etc (Majewski, 2014;Sarvizadeh et al, 2021;Zhou et al, 2022). This article established the relationship between allicin and the improvement of diabetes through the intestinal flora and provided a new idea for human beings to use allicin and improve diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…The main antitumor bioactive substances in garlic, such as Allicin, DAS, DADS, DATS, SAC, and so on, can inhibit the occurrence and development of tumors in the early and late stages of carcinogenesis. Other sulfides, such as SAC, SAMC, Ajoene, and S-methyl-cysteine sulfoxide, combine with DADS and DATS to inhibit tumor cell proliferation by inducing human cell apoptosis (Zhou et al, 2022). The antitumor effect of organic sulfide in garlic is not limited to specific tissues or carcinogens, mainly dependent on allyl and sulfhydryl, and enhanced with the increase of the number of sulfur atoms (C. Lv et al, 2021).…”
Section: The Main Antitumor Components In Garlicmentioning
confidence: 99%
“…Garlic-derived compounds not only directly fight against tumors but also enhance the sensitivity of radiotherapy and chemotherapy, and protect normal cells from carcinogens. Garlic-derived compounds exhibit significant antitumor effects through several mechanisms (Zhou et al, 2022). Firstly, garlic-derived compounds regulate signal pathways by inducing changes in gene expression levels, such as JNK, ENT-related, STAT3, ERK1/2 pathways, and so on.…”
Section: The Epigenetic Pathway Of Garlic-derived Compounds In Increa...mentioning
confidence: 99%